A 5-year single-centre retrospective study of potential drug interactions in burns inpatients with psychiatric comorbidities. Issue 5 (August 2020) - Al-Khalil, Majid; Sack, Anthony; Elson, Rachel; Pleat, Jonathon
Highlights: In theory, severe drug interactions in a psychiatric cohort with burns were common. However, clinical evidence for these complications was lacking. Specific antidepressants were the most commonly implicated drugs already prescribed . Ondansetron and fentanyl were the most frequently implicated new drugs. Serotonin syndrome and arrhythmia were the most common potential adverse events. Abstract: Introduction: Burns patients with psychiatric comorbidities may be at increased risk of harm from drug interactions. We aimed to identify the most common classes of drug involved, the potential clinical effects and any clinical evidence for their occurrence. Methods: The International Burn Injury Database was used to identify all admission episodes for patients with a psychiatric comorbidity over a 5-year period at an adult regional burns unit. For this group, all drugs administered were categorised as either a new or continuing medication. Following this, an established online tool was used to screen for potential interactions between drugs. Where one was identified, a retrospective notes review was used to investigate whether it had occurred clinically. Results: Ninety-one admission episodes were identified and records were available for 60 of these. In total, 145 incidences of severe potential interactions were identified (89 between a new drug and a continuing drug and 56 between two new drugs). The most frequently involved continuing drugs with the potential for interaction were neurotransmitter reuptake-inhibiting antidepressants and mirtazapine, while the most common new drugs identified were ondansetron, fentanyl and tramadol. The most frequently identified potential consequence of interactions were serotonin syndrome, arrhythmias and hypokalaemia. Clinically, there was minimal evidence for any interaction. Conclusion: We have found many potential severe interactions in this patient group and psychotropic drugs were more commonly implicated than other drug classes. However, there was little evidence of the clinical manifestations of interaction. Serious drug interactions in burns patients are likely rare, but clinicians should be aware of the most likely drugs involved and the possible sequelae.